A Cyclobutanol Ring-Expansion Approach to Oxygenated Carbazoles: Total Synthesis of Glycoborine, Carbazomycin A and Carbazomycin B - Natho, Philipp; Allen, Lewis A. T.; Parsons, Philip J. (Synlett, 2023)
The transition-metal-free total syntheses of the oxygenated carbazole natural products glycoborine, carbazomycin A and carbazomycin B are reported. The key step involves an NBS-mediated cyclobutanol ring expansion to 4-tetralones for the preparation of the tricyclic carbazole core.
Keywords: total synthesis; ring expansion; cyclization; antifungal agents; rearrangement